Idiosinkrasi Istri dalam Mencarikan Pasangan Baru Bagi Suami Perspektif Gender - Hikmiyah, Hawa' Hidayatul (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
The ideology of a wife in finding a new wife for her husband is considered to be another behavior of most wives in general. Every wife will not want to be polygamy by her husband, but in contrast to the behavior of the wives in the polygamy community is destiny, the majority of wives in the community are competing in achieving God's blessing by finding a new wife for her husband. The wife's behavior is not in the context of pressure from anywhere, which means finding a new wife for the husband purely from his own initiative. With the afterlife orientation, the wives seek, choose and also prepare the husband's marriage with a new wife. There are several motives that influence the idiosyncracy of these wives, including economic, religious, traditional and political motives. In the gender context of a marriage must meet four indicators namely access must be owned by each husband and wife in the family, get a fair role for what the husband and wife do, exercise the same rights and obligations especially in decision making in the family, and benefit from each other in domestic life. In practice polygamy families will have difficulty meeting the four indicators above. Because initially in the condition of the household not always together so that it will affect access, the division of family roles and responsibilities, especially in making all household decisions. Even though there are several motives in polygamy initiated by the wife, it will still have an impact that is vulnerable to family conflicts. [Idiosinkrasi istri dalam mencarikan pasangan baru bagi suami dianggap sebagai perilaku lain dari kebanyakan istri pada umumnya. Setiap istri tidak akan mau untuk dipoligami oleh suami, akan tetapi berbeda dengan perilaku para istri dalam komunitas poligami adalah takdir, mayoritas istri pada komunitas tersebut berlomba dalam mencapai rida Allah dengan mencarikan istri baru bagi suaminya. Perilaku istri ini tidak dalam konteks tekanan dari manapun, artinya mencarikan istri baru untuk suami murni dari inisiatifnya sendiri. Dengan orientasi akhirat, para istri mencari, memilihkan dan juga mempersiapkan pernikahan suami dengan istri baru. Terdapat beberapa motif yang mempengaruhi idiosinkrasi para istri ini muncul, diantaranya yakni motif ekonomi, religious, tradisi, dan politik. Dalam konteks gender suatu pernikahan harus memenuhi empat indikator yakni akses harus dimiliki oleh masing-masing suami istri dalam keluarga, mendapat peran adil atas apa yang dilakukan suami istri, menjalankan hak dan kewajiban yang sama terlebih dalam pengambilan keputusan dalam keluarga, dan saling memperoleh manfaat dalam kehidupan rumah tangga. Dalam praktik keluarga poligami akan mengalami kesulitan untuk memenuhi empat indikator di atas. Karena awalnya dalam kondisi rumah tangga tidak selalu bersama sehingga akan berpengaruh pada akses, pembagian peran keluarga serta tanggung jawab, terlebih pada pengambilan segala keputusan rumah tangga. Meski terdapat beberapa motif dalam poligami yang diinisiasi oleh istri, tetap akan menimbulkan dampak yang rentan terjadi konflik keluarga.]